2019
DOI: 10.1021/acsomega.8b02879
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydroisoquinoline Sulfamates as Potent Microtubule Disruptors: Synthesis, Antiproliferative and Antitubulin Activity of Dichlorobenzyl-Based Derivatives, and a Tubulin Cocrystal Structure

Abstract: Tetrahydroisoquinoline (THIQ) 6-O-sulfamate-based anticancer agents, inspired by the endogenous steroid 2-methoxyestradiol and its sulfamate derivatives, are further explored for antiproliferative and microtubule disruptor activity. Based on recently designed C3-methyl C7-methoxy-substituted THIQ derivatives, compounds with mono- and dichloro-substitutions on the pendant N-benzyl ring were synthesized and evaluated. Although improved antiproliferative activity was observed, for example, 4a versus 4b and 4b ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Previous studies reported that STX3451 exposure abrogated microtubule structure and function in MDA-MB-231 cells, resulting in a metaphase block [21,43]. STX3451 was successfully co-crystallized with the αβ-tubulin heterodimer, showing its binding to the colchicine site in atomic detail and its sulfamate group interacting with residues beyond the reach of colchicine itself [35].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that STX3451 exposure abrogated microtubule structure and function in MDA-MB-231 cells, resulting in a metaphase block [21,43]. STX3451 was successfully co-crystallized with the αβ-tubulin heterodimer, showing its binding to the colchicine site in atomic detail and its sulfamate group interacting with residues beyond the reach of colchicine itself [35].…”
Section: Discussionmentioning
confidence: 99%
“…This is the first atomic level demonstration of such an interaction for a sulfamate ester. Associated crystallographic work has also demonstrated the effectiveness of STX3451 in binding to the colchicine site [55].…”
Section: Discussionmentioning
confidence: 99%
“…A number of approaches to the design of dual targeting breast cancer agents have been reported e.g., ER/tubulin [ 78 ], tubulin/HSP90 [ 79 ], tubulin/HSP27 [ 80 ], ER/AI e.g., norendoxifen [ 81 , 82 ], and endoxifen [ 83 ], sulfatase/AI [ 84 ], tubulin/sulfatase [ 85 , 86 ] and tubulin/angiogenesis (vascular endothelial growth factor receptor-2 (VEGFR2) [ 87 ]. We now report the synthesis and biological evaluation of a series of 1-(diarylmethyl)-1 H -1,2,4-triazoles, 1-(diarylmethyl)-2 H -1,2,3-triazoles, and 1-(diarylmethyl)-1 H -imidazoles, which are designed as hybrid scaffolds derived from the benzophenone structure of the tubulin targeting phenstatin 7a , together with the 1,2,4-triazole of the aromatase inhibitor letrozole 2 [ 88 ].…”
Section: Introductionmentioning
confidence: 99%